Split Ratings and Differences in Corporate Credit Rating Policy between Moody's and Standard & Poor's. Issue 4 (November 2014) - Bowe, Michael; Larik, Waseem
Abstract This paper investigates split credit ratings awarded by Moody's and Standard & Poor's (S&P) to U.S. corporations. Bivariate probit model estimates, analyzing 5, 238 firm‐year observations from dual‐rated S&P 500/400/600 index‐constituent corporations, indicate firm‐specific financial and governance characteristics predict split ratings. Large, profitable companies with enhanced interest coverage, a greater percentage of independent directors, and more institutional investment are less likely to receive splits. Moody's appears more conservative in its evaluations, assigning lower ratings to smaller, less profitable companies with low interest coverage. Moody's also associates external, independent constraints on managerial autonomy with a higher corporate credit standing relative to S&P.